PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, KOMPENSASI, DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN - Sari, Lady Novia (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the effect of work discipline, work motivation, compensation and non-physical work environment on Griya Muslim and Batik Zam Zam employees. This study uses quantitative methods and uses 2 variables, namely the independent variable and the dependent variable. The population and sample of this study were all employees of Griya Muslim and Batik Zam Zam, as many as 50 people. The results of this study state that compensation, work discipline and motivation have an effect on employee productivity